Climate Change: Readiness Of Sabah Household to Sustain Their Food Availability - Mardiana Muhiddin; Jupikely James Silip; Wan Hurani Osman; Rosmah Murdad; Nor Elliza Tajidin (Faculty of Science & Natural Resources, UMS, 2023)
Climate change makes people more susceptible to sickness, for example; the outbreak of Coronavirus disease (COVID-19) more likely to affected those in places with poor air quality. In other sides, it also affects food supply and distribution due to Movement Control Order (MCO) policy, hence, negatively impact the existing food insecurities situations among household. While urban farming has been used widely by other country to overcome such crisis especially in urban area, we distributed questionnaire and interviews some Tawau individual to determine their food security by observing their involvement in farming activity, food consumption, and finally the relation between edible garden ownership with healthy food consumption during the MCO. The policy force respondents to stocks up food during the phase and 78% of the respondents choose long-lasting type of foods as food stocks, which unconsciously influences their eating pattern during the outbreak. Only 25.9% respondent involve in edible-type garden, however, there are correlation between garden ownership with healthy food intake. This study shows that Tawau household is still relying on market to obtain healthy and fresh food sources. Three major factors that constraint respondents from gardening – no experience or knowledge, limited space and time, and rental issue. By spreading urban farming benefits, it might attract more individuals to involve in farming activities, thus, help improving their household food security especially on fresh and healthy food availability. It is recommended to have in-depth study about factors influence community participation and how urban farming help household secure their food sources daily.